2020
DOI: 10.1159/000509024
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Citrate Dialysis in Hyponatremia: A Case Series

Abstract: Background: Correcting hyponatremia too quickly can lead to osmotic demyelination syndrome. During citrate dialysis, a significant sodium load is brought to the prefilter. We reviewed the impact of this sodium load on the evolution of sodium levels in patients undergoing continuous renal replacement therapy with citrate anticoagulation. Materials and Methods: The medical records of 5 patients with hyponatremia who received dialysis with citrate anticoagulation, over a 10-year period, were reviewed. The sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A mean correction rate of 7.8 mmol/L/24 h in plasma sodium concentration was achieved at the cost of increased labor intensity and concerns over sterility of the modification of dialysate and replacement fluid bags. Furthermore, all the patients in their case series had plasma sodium exceeding 130 mmol/L at CVVHDF initiation in contrast to our current study 8 . The use of standard dialysate and citrate solutions for CVVHD in the management of hyponatremia has not been tested in a clinical study before probably because of concerns over excessive sodium correction due to the high sodium concentration of the citrate anticoagulation fluid.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…A mean correction rate of 7.8 mmol/L/24 h in plasma sodium concentration was achieved at the cost of increased labor intensity and concerns over sterility of the modification of dialysate and replacement fluid bags. Furthermore, all the patients in their case series had plasma sodium exceeding 130 mmol/L at CVVHDF initiation in contrast to our current study 8 . The use of standard dialysate and citrate solutions for CVVHD in the management of hyponatremia has not been tested in a clinical study before probably because of concerns over excessive sodium correction due to the high sodium concentration of the citrate anticoagulation fluid.…”
Section: Discussionmentioning
confidence: 56%
“…The sodium concentration of dialysate and replacement fluids can be modified, although not easily as in intermittent hemodialysis. Previous studies have reported favorable results in the management of hyponatremia with CRRT techniques 6‐8 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations